Novel contactless approach for assessment of venous occlusion plethysmography by video recordings at the green illumination - Alexei A. Kamshilin (Nature Portfolio, 2017)
Abstract Occlusion plethysmography is an important method for assessment of the status of the cardiovascular system, which provides valuable information concerning arterial and venous blood flow, including mechanisms of their regulation. All up-to-date systems estimate change of the limb’s volume during occlusion by contact-type sensors. The objective of the research is demonstration of feasibility of the novel approach to measuring the blood flow during venous occlusion by using imaging photoplethysmography (PPG). Twenty healthy individuals participated in the experiment. We used four synchronized video cameras to record all-around view of the forearm illuminated by the green light. After the recording, the PPG waveform was calculated in more than 4000 non-overlapping Regions of Interest (ROI). In the most of the ROIs, the waveform shape was typical for classical plethysmography with the distinctive linear growth of the signal. Speed of the signal change was the same along the forearm but it varied along the forearm’s circumference. These findings allows us to hypothesize that the PPG waveform is the direct consequence of the forearm blood flow. Therefore, the novel technique could be applied to the same medical examinations as the classical plethysmography, but it is more advantageous because of non-contact nature and easiness in implementation.